Exploring sense of spaciousness in interior settings: Screen-based assessments with eye tracking, and virtual reality evaluations - Tural, Alp; Tural, Elif (Frontiers in Psychology, 2024)
This study investigates the perception of spaciousness in interior environments using screen-based assessments with eye tracking, and virtual reality (VR) technologies. The research explores how four key design elements -view access, view content, materiality, and ceiling geometry- influence perceived spaciousness. Thirty-five college students participated in screen-based and VR-based evaluations of sixteen photorealistic interior settings. Eye tracking data were collected during screen-based assessments to analyze visual attention patterns. Statistical analyses included repeated measures ANOVAs, pairwise comparisons, and correlations between screen and VR assessments. Results showed that view access significantly affected perceived spaciousness in both screen and VR conditions, with larger windows correlating to higher spaciousness ratings. Materiality also demonstrated significant effects, with natural and textured materials perceived as more spacious than concrete surfaces. View content and ceiling geometry showed trends towards influencing spaciousness perception but did not reach statistical significance. VR presentations generally yielded higher spaciousness ratings compared to screen-based presentations, suggesting that immersive technologies may enhance spatial perception. Eye tracking analyses revealed common gaze patterns and variations in visual attention across different design conditions. This study contributes to the understanding of how design elements influence spatial perception and demonstrates the potential of integrating eye tracking and VR technologies in environmental psychology research. The findings have implications for evidence-based design practices aimed at enhancing perceived spaciousness in interior environments.